Evaluation of energy, economics and performance of weeding methods in rice cultivation: Energetics of different weeding methods in rice crop - Borkar, Narayan Totaram; Patel, SP (ORYZA-An International Journal of Rice, 2025)
Weeds pose a major constraint in paddy cultivation, and effective weeding is crucial. Traditional hand weeding is costly, labor-intensive, and time-consuming, whereas mechanical and chemical methods require less labor, time, and cost compared to the traditional approach. Field performance evaluation of different weeding methods revealed that the highest field capacity was observed for the NRRI two-row self-propelled weeder (0.067 ha·h-1), while the lowest was for the finger weeder (0.002 ha·h-1). Similarly, the highest labor requirement was recorded for hand weeding (910 man·h·ha-1), and the lowest for chemical weeding (221.5 man·h·ha-1). The maximum machine energy was required by the NRRI single-row self-propelled weeder (83.27 MJ·ha-1), while hand weeding required the highest total input energy (1439.33 MJ·ha-1). The highest operational cost was associated with the NRRI single-row self-propelled weeder (` 12,533 ha-1), whereas the lowest weeding cost was observed for the commercial power weeder (` 3,328.37 ha-1). The study suggests that traditional weed control methods demand more labor and incur higher costs compared to modern mechanical and chemical alternatives.